2005
DOI: 10.1002/j.1681-4835.2005.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Use of Methods within Information Systems Development Projects

Abstract: The development of information systems has always been and remains a volatile environment. Practitioners and researchers within the field of information systems development (ISD) have put forward a number of different ideas over the past thirty years to better monitor and control the process. The use of traditional ISD methods has been one such idea that has not only achieved widespread application but has garnered many criticisms regarding its application. This study seeks to investigate whether these critici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Authors have sought remedies in the diffusion of methodical professional practice, adapted to accommodate the requirements of the organization and its participants (Kiely and Fitzgerald, 2005), and in adopting effective management practices (Lind, 2000;Lind et al, 2000). Yet, others have been sceptical about the effectiveness of professional IS practice, codified and institutionalized in systems developments methods, to address the particular conditions of organizations in developing countries.…”
Section: Problematization Of Failurementioning
confidence: 99%
“…Authors have sought remedies in the diffusion of methodical professional practice, adapted to accommodate the requirements of the organization and its participants (Kiely and Fitzgerald, 2005), and in adopting effective management practices (Lind, 2000;Lind et al, 2000). Yet, others have been sceptical about the effectiveness of professional IS practice, codified and institutionalized in systems developments methods, to address the particular conditions of organizations in developing countries.…”
Section: Problematization Of Failurementioning
confidence: 99%
“…For instance, Wynekoop & Russo (1997) in a survey of the existing literature on SDMs revealed that over half of the 123 research papers examined consisted of normative research in which concept development was not based on any empirical grounding, but merely on the authors' speculations or opinions. Most field research on methodology use (with the noted exception of Madsen & Kautz, 2002;Fitzgerald et al, 2003;Kiely & Fitzgerald, 2003;Hansen et al, 2003;and Vidgen et al, 2004) has a method engineering and tool orientation that brings focus to structural aspects of the methodology, but without any consideration of organisational issues. Few studies have been conducted in order to identify how SDMs are selected or adapted, or how they are used.…”
Section: A Review Of Related Research On Systems Development Methodsmentioning
confidence: 99%
“…Kiely and Fitzgerald [37] found that traditional information systems development methods were sometimes perceived to be of limited use within modern projects because they are too cumbersome and inflexible. This is the sense in which databases may be considered over-engineered.…”
Section: Failures Of Imaginationmentioning
confidence: 99%